Producing the Precolonial: Professional and Popular Lives of Mapungubwe, 1937-2017 - Ramji, Himal (Department of Historical Studies, 2020)
This thesis is a study of the changing meanings of the thing that is 'Mapungubwe' (most often considered as a thirteenth-century southern African state) within and outside the academy from 1937 and 2017, deliberately excluding meanings that might have existed prior to 1937, analysing the socio-political work Mapungubwe has been made to do in this period. The study explores the shaping and positioning of evidence in the production of narratives that ascribe and/or enforce particular truths or regimes of truth. To do this, I consider the politico-cultural associations that convert an object into evidence of something and make that evidence meaningful. Under what conditions, and for what reasons does this conversion occur? And, what specific meaning is imposed into the object? This is, therefore, an analytical disaggregation and political assessment of the particular signs and symbols through which the composite and contested imaginaire of Mapungubwe has been historically constructed. Necessarily, it is also an unpicking of the languages of evidence. The work is divided into three parts, each dealing with a different strut in the making of Mapungubwe. The first chapter covers the archaeological production of Mapungubwe, from the first excavational work conducted in the 1930s, until more recent work, during the 2010s. During the early twentieth century, the topic of Mapungubwe was cloistered within academic archaeology, particularly at the University of Pretoria. It was only after the end of apartheid that the 'trope' of Mapungubwe began to be deployed in an increasingly wider social realm and integrated into multiple educational and heritage projects, with particular encouragement from the state. The second chapter looks at the introduction and development of the theme of Mapungubwe in the South African national history education curriculum after 2003, when it was also made a UNESCO World Heritage Site and harnessed as name of the Order of Mapungubwe. The chapter analyses the narrative presentation of Mapungubwe in the existing curriculum, and the attending conceptual devices through which this narrative is constructed and sustained. The third chapter scans the explosion of Mapungubwe in popular discourses, about a decade after its strategic foregrounding in school education and institutionalisation as heritage. In this chapter I examine several literary narratives, artistic productions and promotional activities of tourism in conjunction with the current political and economic developments in the area. I make use of sources from various different academic disciplines, including archaeology, history, politics, education and history education, literary theory, as well as relevant samples from fictive writing, sculpture, poetry, touristic longform writing, and advertisements. In bringing together such diverse orders of discourse, the thesis attempts to map the expanding topographies of Mapungubwe - a venture that, I submit, has methodological and topical significance beyond the immediate field of inquiry. Through this work, the reader will be able to see how the language used to describe and inscribe meaning in Mapungubwe has changed over time, exposing the malleability of (precolonial) history in the hands of both professionals and non-professionals. The thesis makes clear to the reader the importance of 'popular' representations of history in the development of modern culture, both in terms of reproducing existing conditions, as well as resisting them. Finally, the thesis troubles the concept of the 'precolonial', and considers what changing purpose the period has had over time, how it shapes our view of history, and how we could alternatively envisage the precolonial and, thus, history.